Desastres naturais ocorridos no estado do Pará nas estações de verão e outono de 2009 - ROCHA, Adriano Souza da (2019)
This study aims to survey the natural disasters in the state of Pará during the rainy season of 2009 and to map and identify the affected municipalities in general causes. In the state of natural disaster to happen every year, cyclical or not. Several factors influenced the occurrence of natural disasters in Para, as its location, because it is located near the equator line, so the period of heavy rainfall is mainly associated with the Intertropical Convergence Zone - ITCZ, which hit the region from early summer (early January) until autumn (March to May). Another factor was the presence of phenomena in these months ENSO (El Nino - Southern Oscillation) in its cold phase (La Niña) in the Pacific and Inter-Hemispheric gradient, with the sign pointing to the southern basin, which also had important roles in intensification of rains. For this study we used data from the Para civil defense, which recorded 53 events in 50 cities of Pará during the study period, these events are characterized by floods and mudslides which are usually associated with precipitation. We also used the rainfall figures that state, from the project RPCH for the rainy season, and images of SST from the NCEP / NOAA. Information through these reviews and discussions were made about the occurrence of these events in the state of Para social justification How this work presents the municipalities affected by natural disasters, recognizing the type of incident and time of occurrence.